Technical report: mathematical modelling of magnetic carrier particle trajectories in blood vessel of patients with cancer / Siti Nor Fatihah Mukhtar - Mukhtar, Siti Nor Fatihah (2017)
Increment in mortality causes by cancer induce researcher for finding new solution in minimizing it. Magnetic Drug Targeting (MDT) is the new therapy for cancer treatment such that it is non-invasive treatment that doesn't require incision of body and at the same time it reduces the side effects from cancer's treatment. The derivation of model for trajectories of magnetic carrier particle based on framework with initial position was obtained. Furthermore, prediction of the volume fraction of magnetic particles required to ensure capture of magnetic carrier particle was also obtained. These models will use Newton's Second law for finding the dominant forces. These forces will be solving by using magnetic dipole moment method and Stokes' law of drag of sphere. Analysis will be resulting to the equation for carrier particle trajectories in blood vessel and prediction of volume fraction required for certain value of radius carrier particle and radius of blood vessel.